2003
DOI: 10.1016/j.crci.2003.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic behaviour of butyl acrylate/styrene/2-hydroxyethyl methacrylate/acrylic acid latices thickened with associative thickeners

Abstract: The rheological behaviour of butyl acrylate/styrene/acrylic acid latices thickened with a hydrophobically modified ethoxylated polyurethane (HEUR) or hydrophobically modified alkali-soluble polyacrylate emulsion (HASE) was investigated. While the pseudoplastic character of frequency dependence of complex viscosity was similar for both thickeners, viscoelastic behaviour, expressed as the ratio of loss and storage moduli, significantly differed, indicating that the HEUR molecules, unlike swollen HASE particles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…The swelling coefficients obtained from all three methods increased as the HEMA content increased, corresponding with previous research (Figure ). It appeared that the synergic effect of swelling occurred when carboxyl groups and hydroxyl groups coexisted in the S/A latex.…”
Section: Results and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The swelling coefficients obtained from all three methods increased as the HEMA content increased, corresponding with previous research (Figure ). It appeared that the synergic effect of swelling occurred when carboxyl groups and hydroxyl groups coexisted in the S/A latex.…”
Section: Results and Discussionsupporting
confidence: 89%
“…HEMA has been used in the medical field because of its stability and hydrophilic properties since hydrogel-formed polymers were introduced in 1960 . Through a hydroxyl group in HEMA, a polymer containing this monomer can interact with water even though hydrophobic monomers are major components of the polymer. The effects of HEMA as a comonomer in S/A latex have been examined, and it has been shown that HEMA can intensify the swelling of S/A latex in alkaline conditions. As most coating processes are performed under alkaline conditions, this swelling would seem to have effects on the coating structure.…”
Section: Introductionmentioning
confidence: 99%
“…The picture is much less clear, however, when one considers a formulated paint, with HEURs and latex (and, potentially, pigments, surfactants, dispersants, and other additives) mixed in water. The original view was that in a paint formulation, HEUR molecules form a transient network of flower micelles, the same way as in solution. ,,, Some of the micelles or individual HEURs can adsorb onto the latex surface, thus connecting the latex particles to the network; the adsorption of HEURs onto latexes has been studied extensively by numerous researchers. Overall, the rheology of the model paint is determined by a complex interplay among the HEUR adsorption onto the latex particles, formation of the micellar network, bridging of the particles by the polymers, and potentially clustering of the particles and the formation of large aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…Quadrat i wspó³pr. [24] zajmowali siê równie¿ zagadnieniem wp³ywu stopnia hydrofobowooeci cz¹stek spoiwa na w³aoeciwooeci lepkosprê¿yste uk³adów spoiwo modyfikator. Autorzy modyfikowali metakrylanem 2-hydroksyetylu powierzchniê cz¹stek spoiwa stano-wi¹cego terpolimer akrylan butylu/styren/kwas akrylowy w celu zwiêkszenia jej hydrofilowooeci.…”
Section: Wp£yw Czynników Niezwi¥zanych Ze Struk-tur¥ Poliuretanowych unclassified